The Flexibility of Institutional Environment and Economic Performance in EU Countries - Svoboda, Ondřej (Vysoká škola báňská-Technická univerzita Ostrava, 2018)
This paper examines the impact of institutional flexibility and institutional quality and their interactions on economic performance. Studies show that while institutional quality reduces transaction market costs, this leads to an immediate but short-term growth in economic growth. On the contrary, the increase in institutional flexibility leads to a steady growth. This paper suggests that past institutional studies place too much emphasis on the stability of institutional settings. The aim of the research is to provide new insights on the issue of institutional flexibility and quality in terms of economic performance. The analytical part of research focuses on the characteristics of the EU states in the period 1996-2016. The results show significant effects of institutional flexibility and quality measures on economic performance.
Flexibilita institucionálního prostředí a ekonomická výkonnost v zemích EU
Keywords: economic performance; European Union; institutional environment; ekonomická výkonnost; Evropská unie; institucionálního prostředí